A 86%‐efficiency CMOS rectifier with an internal threshold voltage cancellation (IVC) scheme. Issue 11 (16th April 2022) - Kim, Byeongseol; Bae, Joonsung
Abstract: In this letter, the authors present a high‐efficiency AC‐to‐DC rectifier for a wireless power transmission system with an internal threshold voltage cancellation (IVC) scheme to improve power conversion efficiency (PCE) and voltage conversion ratio (VCR). The rectifier with the IVC scheme implemented in 0.18‐μm CMOS technology achieves a power efficiency of 86% at a resistive load of 510 Ω when a 13.56‐MHz AC signal with a 6‐V amplitude is applied. In contrast, a previous scheme shows a 58% PCE under the same condition.